Targeting the Neddylation Pathway to Suppress the Growth of Prostate Cancer Cells: Therapeutic Implication for the Men's Cancer. (29th June 2014) - Wang, Xiaofang; Li, Lihui; Liang, Yupei; Li, Chunjie; Zhao, Hu; Ye, Dingwei; Sun, Menghong; Jeong, Lak Shin; Feng, Yan; Fu, Shen; Jia, Lijun; Guo, Xiaomao
Abstract : The neddylation pathway has been recognized as an attractive anticancer target in several malignancies, and its selective inhibitor, MLN4924, has recently advanced to clinical development. However, the anticancer effect of this compound against prostate cancer has not been well investigated. In this study, we demonstrated that the neddylation pathway was functional and targetable in prostate cancer cells. Specific inhibition of this pathway with MLN4924 suppressed the proliferation and clonogenic survival of prostate cancer cells. Mechanistically, MLN4924 treatment inhibited cullin neddylation, inactivated Cullin-RING E3 ligases (CRLs), and led to accumulation of tumor-suppressive CRLs substrates, including cell cycle inhibitors (p21, p27, and WEE1), NF- κ B signaling inhibitor I κ B α, and DNA replication licensing proteins (CDT1 and ORC1). As a result, MLN4924 triggered DNA damage, G2 phase cell cycle arrest, and apoptosis. Taken together, our results demonstrate the effectiveness of targeting the neddylation pathway with MLN4924 in suppressing the growth of prostate cancer cells, implicating a potentially new therapeutic approach for the men's cancer.